The Role of ICS/LABA Fixed-Dose Combinations in the Treatment of Asthma and COPD: Bioequivalence of a Generic Fluticasone Propionate-Salmeterol Device - Tashkin, Donald P.; Ohar, Jill A.; Koltun, Arkady; Allan, Richard; Ward, Jonathan K. (Pulmonary Medicine, 2021)
Both asthma and chronic obstructive pulmonary disease (COPD) are inflammatory chronic respiratory conditions with high rates of morbidity and mortality worldwide. The objectives of this review are to briefly describe the pathophysiology and epidemiology of asthma and COPD, discuss guideline recommendations for uncontrolled disease, and review a new generic option for the treatment of asthma and COPD. Although mild forms of these diseases may be controlled with as-needed pharmacotherapy, uncontrolled or persistent asthma and moderate or severe COPD uncontrolled by bronchodilators with elevated eosinophilia or frequent exacerbations may require intervention with combination therapy with inhaled corticosteroids (ICS) and long-acting beta agonists (LABAs), according to international guidelines. Fixed-dose combinations of ICS/LABA are commonly prescribed for both conditions, with fluticasone propionate (FP) and salmeterol forming a cornerstone of many treatment plans. An oral inhalation powder containing the combination of FP and salmeterol has been available as Advair Diskus® in the United States for almost 20 years, and the first and only substitutable generic version of this product has recently been approved for use: Wixela™ Inhub™. Bioequivalence of Wixela Inhub and Advair Diskus has been established. Furthermore, the Inhub inhaler was shown to be robust and easy to use, suggesting that Wixela Inhub may provide an alternative option to Advair Diskus for patients with asthma or COPD requiring intervention with an ICS/LABA.